Head and neck cancer in HIV patients and their parents: a Danish cohort study - Engsig, F N; Gerstoft, Jan; Kronborg, Gitte; Larsen, Carsten Schade; Pedersen, Gitte; Pedersen, Court; Obel, N (Clinical epidemiology, 2011)
The mechanism for the increased risk of head and neck cancer (HNC) observed in HIV patients is controversial. We hypothesized that family-related risk factors increase the risk of HNC why we estimated the risk of this type of cancer in both HIV patients and their parents. We estimated the cumulative incidence and incidence rate ratios (IRRs) of HNC in 1) a population of all Danish HIV patients identified from the Danish HIV Cohort Study (n = 5053) and a cohort of population controls matched on age and gender (n = 50,530) (study period; 1995-2009) and 2) the parents of HIV patients and population controls (study period 1978-2009). To assess the possible impact of human papilloma virus (HPV)-associated cancers, the sites of squamous cell HNCs were categorized as HPV related, potentially HPV related, and potentially HPV unrelated. Seventeen (0.3%) HIV patients vs 80 (0.2%) population controls were diagnosed with HNC cancer in the observation period. HIV patients had an increased risk of HNC (IRR 3.05 [95% CI 1.81-5.15]). The IRR was considerably increased in HIV patients older than 50 years (adjusted IRR; 4.58 [95% CI 2.24-9.35]), diagnosed after 1995 (adjusted IRR 6.31 [95% CI 2.82-14.08]), previous or current smoker (adjusted IRR 4.51 [95% CI 2.47-8.23]), with baseline CD4 count 350 cells/μL (adjusted IRR; 3.89 [95% CI 1.95-7.78]), and men heterosexually infected with HIV (adjusted IRR 5.54 [95% CI 1.96-15.66]). Fifteen (83%) of the HIV patients diagnosed with HNC were current or former smokers. The IRR of squamous cell HNC in HIV patients was high at HPV-relate sites, potentially HPV-related sites, and potentially HPV-unrelated sites. Both fathers and mothers of HIV patients had an increased risk of HNC (adjusted IRR for fathers 1.78 [95% CI 1.28-2.48], adjusted IRR for mothers 2.07 [95% CI 1.05-4.09]). HIV appears to be a marker of behavioral or family-related risk factors that affect the incidence of HNC in HIV patients.